Desarrollo de las habildades de ortografía en Inglés dentro del proceso de enseñanza-aprendizaje de la escritura instrumental en la escuela primaria - Hernández Armengol, Laura Beatriz (Universidad Central "Marta Abreu" de Las Villas. Departamento Lenguas Extranjeras. Licenciatura en Educación. Especialidad: Lenguas Extranjeras., 2019)
The major paper entitled: “Development of English spelling skill within the teaching- learning process of instrumental writing in Elementary School”, was carried out at “Ernesto Guevara de la Serna”, Elementary School in Santa Clara. The subjects of research had many difficulties regarding English spelling skill. Some empirical methods were administered to get more information about this difficulties. A preliminary proposal of activities to develop English spelling skill whithin the teaching learning process of instrumental writing was designed and implemented during the academic year (2018-2019). The activities were designed taking into account the results of the diagnosis. The proposal was conceived taking into account some theoretical and methodological bases suggested by different authors. Most of the exercises functioned well as the students were motivated as they had the posibility of improving most of their spelling difficulties. The dialectic-materialistic general method was followed, as well as the qualitative approach, mainly the action research methods.

Le document principal intitulé: "Développement des compétences en orthographe anglaise dans le processus d'enseignement-apprentissage de l'écriture instrumentale à l'école primaire" a été réalisé à l'école primaire "Ernesto Guevara de la Serna" à Santa Clara. Les sujets de recherche ont eu beaucoup de difficultés en ce qui concerne les compétences en orthographe anglaise. Certaines méthodes empiriques ont été utilisées pour obtenir plus d'informations sur ces difficultés. Au cours de l'année universitaire (2018-2019), une proposition préliminaire d'activités visant à développer les compétences en orthographe anglaise dans le processus d'enseignement et d'apprentissage de l'écriture instrumentale a été conçue et mise en œuvre. Les activités ont été conçues en tenant compte des résultats du diagnostic. La proposition a été conçue en tenant compte des bases théoriques et méthodologiques suggérées par différents auteurs. La plupart des exercices ont bien fonctionné car les étudiants étaient motivés, car ils avaient la possibilité d’améliorer la plupart de leurs problèmes d’orthographe. Le méthode dialectico- matérialiste générale a été suivie, de même que l'approche qualitative, principalement les méthodes de recherche-action.
Keywords: Educación Primaria; Lengua Extranjera; Lengua Inglesa; Enseñanza de Lenguas; Ortografía; Enseñanza de Idiomas; Proceso de Aprendizaje